Association Between Poverty and Intestinal Parasitism in Pre-School, Elementary School Children and Adolescents from South of Valencia, State of Carabobo, Venezuela - Liseti Solano; Iraima Acuña; María Barón; Alba Morón de Salim; Armando Sánchez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2008)
Poor living conditions, fecal contamination of food, water and soil are factors that contribute to intestinal parasites transmission. In order to stablish association between poverty and parasitary infectation, socio-sanitary (family structure, social stratum, housing), environmental (water and excreta disposition) and coproparasitological (direct and kato examination) aspects were evaluated, in 257 subjects (2-18 years old), from Valencia, Carabobo State. Findings were: High prevalence of school children, of stratum IV, of monofamiliar structure, with five persons per group. Parasite infestation was found in 48.2% of children, more prevalent in school children, with mono (53.7%) and poliparasitism (52.6%). Protozoa forms were more prevalent in stratum IV (63.9%) and helminthes forms in stratum V (64.3%). There was not statistically significant association between socioeconomic strata assessed by Graffar-Méndez Castellano method and parasitic infestation, but between parasitic infestation and sociosanitary conditions (absence of sewers, non-treated water, intradomiciliary bath, absence of floor and number of people by family), statistically significant association was present. Predominance of protozoa in subjects from small families groups (less than five persons) was 56.6% while in children from large families groups (higher than five persons), prevalence of helminthes was 78.6%. Significant association was found between Blastocystis hominis, Entamoeba coli and Ascaris lumbricoides and large families groups. It is concluded that a strong and significant association was found between parasite infestations and socio-sanitary, environmental and cultural conditions, situation that favours a high morbidity rate, which perpetuates the interactions cycle of poverty and parasite infestations.